Pengaruh penempatan, pendidikan dan pelatihan terhadap kinerja pegawai satuan kerja penataan bangunan dan lingkungan Direktorat Jenderal Cipta Karya Kementerian Pekerjaan Umum Propinsi Riau - Dimas Dwi Prasetyo; Sri Indarti; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research conducted to find out the effect of job position, education’s level and job training toward actual performance of PBL’s civil servants on Public Ministery at Riau province.There are 35 civil servants of PBL use as sample, and randomly sampling use in thisresearch. The instruments of this research are questionnaires and interview. The data analyze by using descriptive quantitative and liniear regression.Based on the research finding, there is effect of job position, education’s level and job training toward actual performance. Besides, not only job position influences toward actual performance partially, but also education’s level and job training toward actual performance of PBL’s civil servants on Public Ministery at Riau province partially.Key Word: Job Position, Education’s Level, Job Training, Actual Performance